MYTH OF EUROPEAN VAMPIRES IN JOHN AJVIDE LINDQVIST’S LET THE RIGHT ONE IN - Sylvia Yulita Kamal (STBA Prayoga Padang, 2020)
ABSTRACT This research aims to analyze the Myth of European Vampires in John Ajvide Lindqvist’s Let The Right One In. There are two kinds of European Vampire myth analyzed in this research. First is the myth of European Vampire characteristics which are reflected by Eli. Second is the myth of human- vampire transformation which is reflected by Virginia. Two problems appear to discuss in this research; the myth of the kinds of vampire characteristics and the myth of human-vampire transformation. The Vampire myth theories from Jay Stevenson Ph. D. and Sebastian Condado de Haza were utilized in this research.There are two concepts used in this research. They are the European Vampire characteristics concept and Human-Vampire transformation concept. A qualitative descriptive method was applied to analyze Eli’s character as a vampire and Virginia’s character as a human-vampire by finding relevant quotations. The result of this research proves the myth about European vampire characteristics by Eli and the myth of human-vampire transformation issues by Virginia. There are two criteria of European vampire characteristics categories indicating Eli as a vampire; general characteristics and physical characteristics.Meanwhile, three steps of the human-vampire transformation myth can explain the suffering of human-vampire that are perceived by Virginia, which are vampire bite, depression, and suicide.